Prolonged Hypercalcemia Following Resection of Dysgerminoma: A Case Report - Abigail Wald; Sumana Narasimhan; Lucybeth Nieves-Arriba; Steven Waggoner (Obstetrics and Gynecology International)
Background. Hypercalcemia is a rare but potentially dangerous complication of pediatric cancer. Of the dysgerminoma cases reported to date, associated hypercalcemia is corrected within 2–7 days of tumor resection. Case. A 13-year-old female with an ovarian dysgerminoma was found to be hypercalcemic on presentation. Following dysgerminoma resection, moderate hypercaclemia persisted for 7 days and calcium remained mildly elevated for an additional 7 days. PTHrP was undetectable. Immunolocalization studies indicated that 1𝛼-hydroxylase was expressed in dysgerminoma tissue but 1,25(OH)2D3 was not elevated. Conclusion. Persistently elevated calcium levels following tumor resection suggests that this case involves a previously undescribed mechanism. Elucidation of this mechanism may offer new insights into tumor biology and opportunities for therapeutic correction of hypercalcemia in this patient population.